Trajectory of coastal wetland soil physical and microbial properties 6+ years after thin layer placement sediment amendment - Cheng, Jacob Z.; Berkowitz, Jacob F.; White, John R. (Frontiers in Ecology and Evolution, 2025)
The intentional thin layer placement (TLP) of dredged sediment is an increasingly popular approach to maintaining marsh elevation and restoring degraded marshes, which can improve conditions for vegetation establishment. Prior TLP restoration projects, assessed shortly after construction, evaluated soil, hydrology, plant, and faunal responses. However, few long-term studies (>3 yrs) investigate TLP-induced shifts in soil properties and especially properties related to biogeochemical cycling. In response, this study revisited a salt marsh 6+ years after TLP restoration and determined both soil physiochemical and microbial properties related to plant growth (nitrogen (N) mineralization) and water quality improvement (denitrification). Data were compared with samples collected before TLP project implementation and 0.5 years after project completion. Bulk density increased to 342% of the control 0.5 years after project completion and was 272% of the control after 6+ years, suggesting significant sediment retention in the marsh over time. Microbial biomass declined to 7.6% of the control following TLP, then rebounded to 29.4% of control after 6+ years. The N mineralization rate increased from 22% to 31% of control after 0.5 years and 6+ years, respectively. Notably, live root density was 3x higher in the TLP marsh compared with the control, suggesting that the restored marsh likely responded to reduced nutrient availability (approximately 1/3) by generating additional belowground biomass. TLP marsh denitrification rates were not significantly different from the control suggesting the water quality improvement ecosystem services recovers more quickly than other soil properties. While TLP soil properties appear to be trending more similar to controls over time, longer-term studies are needed to inform the ecological trajectories of sediment amended marshes.